Analysis of high-tech exports on the example of Lithuania: influence of the cyclic component (Economics and region, 2023)
The article proposes the author's methodology for analyzing the structure of the dynamics of the export of high-tech products as a tool for state regulation in the field of innovation and scientific and technical development. The methodology reveals the economic meaning and allows to distinguish the following components in the structure of the dynamics of the export of high-tech products: uniform growth; accelerated growth; cyclical growth. And it also allows us to consider how the share of the impact of the cyclical component changes, if high-tech exports are considered as a share of all industrial exports and as a share of GDP, and also compared with the structure of the country's GDP dynamics as a whole. The work examines the structure of the dynamics of high-tech exports on the example of Lithuania, which is a relatively late member of the European Union and a country that underwent economic transformations after the collapse of the Soviet Union. The analysis of high-tech exports in the country was carried out and the dynamics of high-tech exports and the structure of export growth were interpreted in order to assess the prospects for overall economic growth in the country. High-tech exports in Lithuania have certain constant growth rates, the influence of which on the dynamics increases linearly. It can be noted that in the dynamics of high-tech exports there is a strong influence of cyclical components. These cycles have oscillation periods of 5,8 years, which indicates the influence of short-term processes. Cycles can reflect, on the one hand, the life cycle of the creation, introduction and entry into the world market of new types of high-tech goods and, on the other hand, the market situation, the demand for these products from national manufacturers. The authors analyzed cycles in the dynamics of high-tech exports in Lithuania with a period of 5,8 years and calculated the level of influence of the cyclical component on the general trend. The article is an integral part of the study, which also analyzes other countries with a high global level of high-tech exports according to the author's proposed methodology.
Keywords: R&D; high-tech products; export; mathematical modeling; dynamic indicators